2019
DOI: 10.1038/s41598-019-40338-7
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell secretion of miR-375 to HDL is inversely associated with insulin secretion

Abstract: Extracellular microRNAs (miRNAs) are a new class of biomarkers for cellular phenotypes and disease, and are bioactive signals within intercellular communication networks. Previously, we reported that miRNAs are secreted from macrophage to high-density lipoproteins (HDL) and delivered to recipient cells to regulate gene expression. Despite the potential importance of HDL-miRNAs, regulation of HDL-miRNA export from cells has not been fully studied. Here, we report that pancreatic islets and beta cells abundantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Studies have shown that in human type 2 diabetes and other rodent models with diabetes, the level of extracellular miR-375-3p is affected. Nevertheless, in both humans with type 1 diabetes (T1D) and murine models of T1D, miR-375-3p was consistently found to be upregulated in plasma samples [ 30 ]. The circulating level of miR-375 may reflect changes in β -cells and may be changed in the blood of patients recently diagnosed with T1D [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in human type 2 diabetes and other rodent models with diabetes, the level of extracellular miR-375-3p is affected. Nevertheless, in both humans with type 1 diabetes (T1D) and murine models of T1D, miR-375-3p was consistently found to be upregulated in plasma samples [ 30 ]. The circulating level of miR-375 may reflect changes in β -cells and may be changed in the blood of patients recently diagnosed with T1D [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overexpression of miR-127 is known to promote mesendoderm generation via nodal signaling [54]. miR-709, a miRNA predominant in pancreatic β-cell-derived exosomes [55], targets different genes in different tissues [47]. For example, in a peripheral nervous system injury, it targets the Egr2, c-Jun, and Sox-2 transcription factors [56], whereas in adipocytes, it mediates glycogen synthase kinase-3β downregulation, which activates Wnt/β-catenin signaling [57].…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be an overwhelming need for high-quality human islets for a myriad of research studies attempting to understand and treat diabetes. Human islets are a staple for diabetes investigators working on a wide range of experiments, from developing new diagnostic tools 31 , including new chip technology 32 , to prototypes for encapsulation studies 33 , 34 , alternate transplant sites 35 , 36 , selection of biomaterials for implants 37 , and basic science for the understanding of islet physiology 38 , 39 . As the need for human islets increases with the rise in the number of studies requiring them, islet distribution organizations need to be cognizant of variables that influence islet recovery and function.…”
Section: Discussionmentioning
confidence: 99%